2010
DOI: 10.1249/mss.0b013e3181b18fb8
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training with Vascular Occlusion in Inclusion Body Myositis

Abstract: We describe a novel, and likely the first, nonpharmacological therapeutic tool that might be able to counteract the muscle atrophy and the declining strength that usually occur in IBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 19 publications
(26 reference statements)
3
93
0
6
Order By: Relevance
“…We have found that after a 12-wk training program, an IBM patient's leg press one-repetition maximum, balance and mobility function, and thigh cross-sectional area increased 15.9%, 60%, and 4.7%, respectively. Health Survey Questionnaire subscales demonstrated improvements ranging from 18% to 600% and mRNA expression of mechanogrowth factor increased 3.97-fold, whereas that of atrogin-1 decreased 0.62-fold 4,5 . This video describes in details the protocol of a resistance training program with vascular occlusion for this population.…”
Section: Discussionmentioning
confidence: 98%
“…We have found that after a 12-wk training program, an IBM patient's leg press one-repetition maximum, balance and mobility function, and thigh cross-sectional area increased 15.9%, 60%, and 4.7%, respectively. Health Survey Questionnaire subscales demonstrated improvements ranging from 18% to 600% and mRNA expression of mechanogrowth factor increased 3.97-fold, whereas that of atrogin-1 decreased 0.62-fold 4,5 . This video describes in details the protocol of a resistance training program with vascular occlusion for this population.…”
Section: Discussionmentioning
confidence: 98%
“…In another context, in a case report about an individual with inclusion body myositis, our group recently demonstrated that lower limb RE (knee extension) with VO for 12 weeks induced an increase of 11.6% in one repetition maximum strength tests (1RM), of 60% in mobility and of 4.7% in thigh CSA. Importantly, no side effects were observed (47).…”
Section: Resistance Exercise With Vascular Occlusionmentioning
confidence: 91%
“…Some studies have analysed the activity of mTOR [1, 2,12,13] or the expression of mRNA [47,48] for this specific protein and its targets downstream and upstream.…”
Section: Mtor Signalling Pathwaymentioning
confidence: 99%